A study on single tree modeling for wind-induced fluid–structure Interaction. Exploring the level of detail for tree representation. - Perumadan Mannummal, John Paul (My University, 2025)
Trees and green spaces are vital for sustainable urban living, yet tools to guide optimal tree placement and assess wind related risks remain limited. This study presents a numerical modeling framework for simulating wind-induced fluid-structure interaction (FSI) on a single tree. Three tree models of increasing level of detail (LoD) are developed, and detailed FEM and CFD parameter studies are conducted to identify key mechanical and aerodynamic properties. Rather than relying on a detailed CAD model, the tree geometry is defined through spatial functions, allowing for the assignment of material and permeability properties to stem and crown regions within a single mesh used by both solvers. The immersed boundary method (IBM) is employed to capture tree motion in the CFD simulations. Through FEM parameter studies, a set of material properties for the artificial crown is proposed, identifying that a stiffness on the order of 102 Pa is necessary to observe wind-induced deformations. The study also evaluated how modeling the stem as a permeable object rather than a solid body affects the aerodynamic forces and wake properties. It was found that a permeable stem yields aerodynamic forces and velocity fields comparable to those of a solid stem. However, for both types of stem, the aerodynamic influence of the stem is confined to its immediate vicinity. Beyond the crown’s radial extent, the presence or absence of a stem showed negligible impact on the flow field. The results further highlight the dominant role of crown permeability in determining aerodynamic loading and wake characteristics, underscoring the importance of measurement-based permeability inputs for crown. Overall, the study demonstrates the feasibility and current limitations of the proposed modeling approach, providing a foundation for future FSI based tree–wind interaction studies.
Keywords: Tree Modeling; Tree-Crown Modeling; Tree-Crown Modeling; Level of Detail; Wind-Tree Interaction; Fluid Structure Interaction; CFD; FEM